2019
DOI: 10.1016/j.ijpharm.2019.118601
|View full text |Cite
|
Sign up to set email alerts
|

Spray-dried anti-Campylobacter bacteriophage CP30A powder suitable for global distribution without cold chain infrastructure

Abstract: Campylobacter jejuni is a leading cause of foodborne illness globally. In this study, a spray drying and packaging process was developed to produce a thermally-stable dry powder containing bacteriophages that retains biological activity against C. jejuni after long distance shipping at ambient temperature. Spray drying using a twin-fluid atomizer resulted in significantly less (p < 0.05) titer reduction than spray drying using a vibrating mesh 2 nebulizer. The use of centrifugation and dilution of filtered bac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 44 publications
(51 reference statements)
1
18
0
Order By: Relevance
“…The lyophilized product showed a typical moisture content of 13% after 24 hours of lyophilization, measured by TGA. The excipient formulation of leucine and trehalose described in a previous spray-drying study [26] showed a 1.22 ± 0.07 log10 PFU mL-1 titer reduction following lyophilization (Figure 2A). We further examined alternative excipients to maintain the phage titer more effectively during lyophilization.…”
Section: Phage Cp30a Supplemented With Tryptone Retained the Highest mentioning
confidence: 72%
See 3 more Smart Citations
“…The lyophilized product showed a typical moisture content of 13% after 24 hours of lyophilization, measured by TGA. The excipient formulation of leucine and trehalose described in a previous spray-drying study [26] showed a 1.22 ± 0.07 log10 PFU mL-1 titer reduction following lyophilization (Figure 2A). We further examined alternative excipients to maintain the phage titer more effectively during lyophilization.…”
Section: Phage Cp30a Supplemented With Tryptone Retained the Highest mentioning
confidence: 72%
“…To our knowledge, this is the first study to report the stability of lyophilized Campylobacter phage and where the small titer loss upon lyophilization is favorable compared to other studies of bacteria-specific phages [34]. Future work could explore alternative excipients, especially the formulation of trileucine and pullulan that have enhanced the performance of the spray-drying technique to stabilize phage titers [26]. Further study could also focus on the application of secondary drying at warmer temperatures to desorb any bound water present after primary drying to reduce the residual moisture content.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…87) A similar phenomenon is seen with endolysins; however, a recent report indicates that the engineering of an endolysin in order to add an albumin-binding domain extended the half-life of the endolysin. 88) Another area that could become relevant, if phage therapy advances toward widespread use, is the study of storage conditions and administration routes. For example, even though phages are considered relatively stable, being able to unequivocally guarantee their stability under different conditions would be useful.…”
Section: Future Challenges and Projectionsmentioning
confidence: 99%